The Lost Message of Nils Strindberg: Re-examining an 1897 Andrée Balloon Expedition Mystery - Lantz, Björn; Uusma, Bea; Tjernström, Michael (Polar Record, 2024)
During the ill-fated 1897 Andrée balloon expedition, Nils Strindberg allegedly dropped a small tin containing a last message for his fiancée onto the island Fuglesongen in northwestern Svalbard, as the expedition crew passed over it in their hydrogen balloon, Örnen. Despite at least one lengthy search on Fuglesongen, the tin has never been found. This paper investigates the hypothesis that the tin was accidentally dropped onto Klovningen, a neighboring island similar in size and shape, situated approximately 2.4 km east of Fuglesongen. A re-analysis of Strindberg’s original handwritten notes from the balloon flight, along with other primary sources and meteorological analyses, suggests that a targeted search for the tin on Klovningen could be a promising next step in solving this enduring mystery.